Store brands' purchase intention: Examining the role of perceived quality - Cristina Calvo-Porral; Jean-Pierre Lévy-Mangin (European Research on Management and Business Economics (ERMBE), 2017)
Considering the increase of the store brand's market share globally, the present study addresses the following question: “Does the consumer product perceived quality influence store brands' proneness?”; or in other words “Does product perceived quality influence store brands' purchase intention?”, since perceived quality is a customer-based undertaken variable. The present study proposes and empirically tests a conceptual model of the influence of perceived product quality of store brands relative to perceived value and purchase intention. Structural Equation Modelling (SEM) was developed on a sample of 439 consumers, distinguishing between consumers with high perceived quality (HPQ) and low perceived quality (LPQ). Our findings highlight that store brands' purchase intention is strongly influenced by confidence for both HPQ and LPQ customers, followed by product price. Additionally, our results suggest the moderating role of perceived quality on some of the proposed relationships. Store brand managers and retailers could develop market segmentation and perform marketing strategies based on customers' perceived quality.
Keywords: M30; L81; 650; Store brands; Perceived quality; Purchase intention; Confidence; Price